Toward an Investigation of Diversity and Cultivation of Rye (Secale cereale ssp. cereale L.) in Germany: Methodological Insights and First Results from Early Modern Plant Material - Sofia Filatova; Benjamin Claassen; Guillermo Torres; Ben Krause-Kyora; Eva Holtgrewe Stukenbrock; Wiebke Kirleis (Agronomy, 2021)
Rye (Secale cereale ssp. cereale L.) is a secondary domesticate, considered to have originated as a weed in wheat fields and to have developed traits of domestication by evolving similar physiological and morphological characteristics to those of wheat. Although it migrated into Europe as a weed possessing domestication traits, it became one of the most significant crops grown in large parts of Europe from the medieval period onward. Within the modern borders of Germany, rye was grown using at least two divergent cultivation practices: eternal rye monoculture and three-field rotation. The straw of rye was used to produce Wellerhölzer, which are construction components in traditional half-timbered houses that have enabled a desiccated preservation of the plant remains. In order to assess the impact of cultivation practices, local environmental conditions and genetic variation on the genetic diversification of rye, we seek to integrate well-established archaeobotanical methods with aDNA sequencing of desiccated plant remains obtained from Wellerhölzer from Germany. In the current contribution, we present a proof of concept, based on the analysis of plant remains from a Wellerholz from the Old Town Hall of Göttingen. We use arable weed ecology to reconstruct cultivation practices and local environmental conditions and present a phylogenetic analysis based on targeted loci of the chloroplast and nuclear genome. Our results emphasise that the study of desiccated remains of plants from Wellerhölzer offer a unique opportunity for an integration of archaeobotanical reconstructions of cultivation practices and local environment and the sequencing of aDNA.